Pemahaman dan Aplikasi Nilai-Nilai Adab Makan dan Minum Melalui Animasi Kartun Islami Di RA El Syarifah Medan - Syarifah Mardiah; Munisa Munisa (Departement of Mathematics Education, 2023)
This research aims to analyze the use of Islamic cartoon animation in internalizing the values of proper eating and drinking etiquette among students at RA El Syarifah in Medan. Given the significance of Islamic education in shaping individual character and morality, particularly in early childhood education (PAUD), and the recognition of the potential of media as a learning tool, this study will assess the extent to which Islamic cartoon animation enriches the learning process of eating and drinking etiquette values. Additionally, the study aims to identify the factors influencing the internalization of these values through animated media. This research employs a descriptive qualitative method with the primary objective of thoroughly investigating and describing the situation under study in-depth and comprehensively. The subjects of this study are students at RA El Syarifah Medan. Data collection techniques include observation, interviews, and documentation. Interviews with teachers are conducted to understand the eating habits of students, both before and after meals. Data analysis employs the steps of data collection, reduction, presentation, and conclusion drawing. The findings of the study indicate that introducing Islamic etiquette related to eating and drinking through the Nussa and Rara video series effectively shapes religious character in students. This process occurs not only during the dissemination of knowledge but also through the role modeling of teachers and everyday practices in eating and drinking that align with etiquette. Consistency in applying moral values related to eating and drinking also plays a key role in religious character formation. The examples provided by teachers significantly contribute to the success of this process. Meal times serve as effective moments for students to apply the knowledge they have learned, in line with their cognitive development stage. This research makes a significant contribution by demonstrating that religious character can be instilled from an early age through everyday activities, particularly in eating and drinking, relying on Islamic teachings. Character formation requires not only knowledge but also habitual practice and guidance from teachers as role models. These findings are expected to serve as a foundation for further research in the context of developing Islamic religious education for early childhood.